Cinematography for female objectification: Analysis of item songs of Pakistani movies - Aksar, Iffat; Jiang, Xuege; Gong, Jiankun (Frontiers in Communication, 2022)
The transition in Pakistani cinema and terming it as a rival of cinema heavily depends on the bowing technique of item songs, which is deliberately fueling the negative representation of females. The qualitative analysis of item songs underlines the representation of women and sheds light on aspects regarding how the objectification of women in item songs is done in a patriarchal society and what values are assigned based on gender. The analysis of item songs revealed that women were sexually objectified and the use of clothing, jewelery, makeup, body movements, and gestures are filmed to enhance their bodies. Hence, most of the songs used females as an object of sensation and enjoyment. On the other side, the notion of women's empowerment is being raised all over the world but still, cinema presents her in a submissive way and defines her role to please men. The dominancy of the male is projected and the close angle of her body gestures and nude body parts show her vulnerability. The visualization of the female reflects that she is presented tactfully to appeal to the audience, and her fragile role is reinforced.